2021
DOI: 10.1155/2021/4847112
|View full text |Cite
|
Sign up to set email alerts
|

Familial Aggregation and Heritability of Myopia: A Local Population Survey in Shanxi, China

Abstract: Purpose. To further determine the roles of environmental and genetic factors in the development of myopia, a comprehensive survey was performed. The guidance for myopia-susceptible people is established which might help prevent or delay the onset and development of myopia. Methods. 1,852 students were recruited using the multistage sampling approach from the Gaoping county in Shanxi. The refractive status of students was examined using an autorefractometer, and the refractive status of students’ first-degree r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The goal of this research is to determine whether environmental factors that affect myopic development, which include performing near-work activity, or biological factors, which consist mainly of heritable genetic components, have a greater influence on the development of myopia in an individual. This paper follows a mixedmethod correlational method and aligns most closely with the methodology of Wang and Bi (2021), which researched familial aggregation and heritability of myopia, and consisted of an eye-screening for each participant to determine eye prescription, and later a questionnaire that would ask the participants about whether or not their siblings or parents also suffered from myopia, as well as the severity of their myopia. Additionally, the foundational work of Huang et al (2019), was crucial to the development of the researcher's methodology.…”
Section: Methodsmentioning
confidence: 99%
“…The goal of this research is to determine whether environmental factors that affect myopic development, which include performing near-work activity, or biological factors, which consist mainly of heritable genetic components, have a greater influence on the development of myopia in an individual. This paper follows a mixedmethod correlational method and aligns most closely with the methodology of Wang and Bi (2021), which researched familial aggregation and heritability of myopia, and consisted of an eye-screening for each participant to determine eye prescription, and later a questionnaire that would ask the participants about whether or not their siblings or parents also suffered from myopia, as well as the severity of their myopia. Additionally, the foundational work of Huang et al (2019), was crucial to the development of the researcher's methodology.…”
Section: Methodsmentioning
confidence: 99%
“…Existing studies have shown that children health statuses were strongly influenced by parents’ health knowledge [ 22 ] and parental health genetics [ 23 ], such as the occurrence of hypertension [ 24 ] and myopia [ 25 ]. On one hand, existing studies showed that grandparents’ care could exert a positive effect on the health status of their grandchildren [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%